Reliance Foundation launches Jio Institute - Reliance Industries Limited (2022)
Reliance Foundation launches the first ever batch of 2022-23 PGP (Post Graduate Programme) at Jio Institute in the month of July. The Institute launched two programs Artificial Intelligence & Data Science and Digital Media & Marketing Communication in its initial phase. The inauguration event of Jio Institute was held on 20th July and was attended by Chancellor Dr. R.A. Mashelkar, Vice-Chancellor Dr. Dipak Jain, and Director Dr. Palak Sheth of Jio Institute.